The Application of Modern Digital Design and Manufacturing Technologies in Sports Equipment Design - Tian, Wenjun (International Journal of Mechanical and Electrical Engineering, 2025)
The integration of digital design and manufacturing technologies has revolutionized sports equipment production, improving efficiency, precision, and customization. This study explores the role of CAD, CAE, and 3D printing in enhancing design accuracy and reducing development cycles, while highlighting intelligent manufacturing’s impact on cost reduction and resource optimization. Personalized equipment production, driven by 3D printing and consumer data, is examined alongside simulation technologies for performance testing and iterative optimization. Furthermore, real-time data feedback and lifecycle management systems demonstrate the potential for sustainable and adaptive designs. These advancements redefine industry standards, fostering innovation, sustainability, and user-centric development in sports equipment manufacturing.